Meta-Analisis Hubungan Motivasi Belajar dan Hasil Belajar Matematika Siswa di Indonesia - Samritin Samritin (Journal on Education, 2019)
Learning motivation is an essential element for a student in learning mathematics. Mathematics learning achievement is closely related to learning motivation. This study analyzes the relationship between the two variables using a meta-analysis design. Meta-analysis was carried out using the help of the JASP computer program, while data searches used Harzing’s Publih or Perish that was indexing by Google Scholar. The data analyzed as a sample were 11 studies at the elementary, junior high, and high school levels. Based on the results of data analysis, it was found that the effect sizes of the 11 studies analyzed varied. The results of this study found that the correlation coefficient rE was 0.452 with a p-value <0.001 at the 95% confidence level. While the results of the analysis of moderator variables at the school level and study period respectively, obtained p-value = 0.008 with Qb = 9.641 and 0.036 with Qb = 4.441. Based on the results of the data analysis, this study concluded that there was a significant positive relationship between learning motivation and students' mathematics learning outcomes in Indonesia. The relationship differed significantly between school levels and between publication period. The research findings have implications for the need for serious attention from teachers, principals, parents of students, and related parties to always maintain and continue to arouse students' learning motivation in learning mathematics. on increasing student motivation.